Melindungi Permata Biru: Kolaborasi Masyarakat Sumbawa dalam Konservasi Penyu dan Habitat Terumbu Karang - Medina Arrahman; Yanti Meriska (Lembaga Publikasi Ilmiah Nusantara, 2026)
The destruction of coastal ecosystems on Sumbawa Island due to destructive activities threatens the conservation of sea turtles and coral reef habitats known as the